Large eddy simulation of turbulent partially premixed flames in oxy-fuel combustor under subcritical and supercritical conditions - Keum, Kyeongchan; Park, Youchan; Lee, Hakseon; Chang, Sungho; Do, Hyungrok; Lee, Dae Keun; Kang, Seongwon (Journal of mechanical science and technology, 2022)
A supercritical CO 2 -diluted oxy-fuel combustor was analyzed focusing on the flame structure and stability. A parametric study on the background pressure (20–115 bar) was performed for swirl-stabilized combustion using large eddy simulation (LES) with a detailed finite-rate chemistry model. The employed physical conditions match those of an experiment. The differences between the subcritical and supercritical states were analyzed in terms of the mixing and reaction characteristics as well as the flame stability. Also, the 1-D simulations were performed to examine the basic reaction characteristics and evaluate different kinetic mechanisms in the supercritical conditions. Different turbulent flame structures between the subcritical and supercritical states could be explained using the swirl number and Reynolds number affected by a viscosity change. The flame stability was analyzed using the instantaneous and RMS flow fields, Rayleigh criterion, flame brush thickness, mean shear rate, and heat release. Relatively improved flame stability was observed in the supercritical state. The flame brush thickness and turbulent intensity are proportional and decrease as the background pressure increases.